Marketing Class Consciousness in A Passage to India: A Marxist Analysis - Yasir khan (University of Chitral Journal of Linguistics and Literature, 2023)
The present paper is aimed to analyze the novel A Passage to India from the Marxist perspective. For the analysis the major theoretical insights have been taken from Marxist critics including Luckas (1968) and Antonio Gramci (1988). The analysis is thematic in nature. Generally, we see that Marxist criticism takes in consideration that the capitalist society is divided into haves and haves not. Lucaks (1968) considers that Marxist ideology can be extended from mere class conflicts to the class and caste system, gender, and race also. Therefore, this analysis has been extended from the simple Marxist category of class conflicts to the exploitation of the underdeveloped and developed, colonizer and the colonized, religion as well. Gramcian model Marxist criticism considers ideology as superstructure and state apparatuses as discursive tools of exploitation. In relation to Marxist critique, we see that the relationship of both bourgeoisie and proletariat classes is parallel to the colonizer and colonized in imperialist conditions. At present Marxist criticism also includes the slavery as an outcome of socio and economic un-equality. Marxist criticism counts religion as a marker of raising class consciousness. It has been found in the study that as the English people and administrative were the men of resources in India. The English had exploited the Indians on account of being without resources. In the conclusion, A Passage to India as a piece of literature represents the ideological and class-based relations based on economic relations.